THE PREPOSITION NGANTI IN JAVANESE LANGUAGE - Wulandari, Ari (ELTICS Journal, 2015)
AbstractThis essay is under auspice of structural linguistics, which is mean to describe the preposition nganti in Javanese language, understanding, how to use, what kind of categorial coconstituent which is determined the presence, what is function, and what semantic role of prepositional phrases. Therefore, this essay uses descriptive qualitative method and a contact approach. This essay shows the result the presence of the preposition nganti in the sentence is not determined by the filler predicates category, but is determined by the coconstituent category which can be seen from the use. Categorical types of constituents that determine the presence of the preposition nganti are five categories, namely nouns (concrete, abstract), adjectives, numerals, adverbs (temporal, qualitative, size), and verbs (active, adversative). The preposition nganti function is as a boundary ending marker (time, place, number, size), a purpose marker, and an effect marker. Â  Key words: preposition nganti, Javanese language, structural linguistic, coconstituent, category, function, marker